Surface/edge functionalized boron nitride quantum dots: Spectroscopic fingerprint of bandgap modification by chemical functionalization. Issue 1 (January 2020) - Angizi, Shayan; Shayeganfar, Farzaneh; Azar, Mahdi Hasanzadeh; Simchi, Abdolreza
Abstract: Promising properties of boron nitride nanomaterials such as their chemical, thermal, and mechanical stability have made them suitable materials in a various range of applications. However, their low electrical conductivity and wide bandgap, particularly in the case of boron nitride quantum dots (BNQDs), have given rise to severe limitations. Efforts on bandgap engineering through doping and surface functionalization have gained little success due to their high thermodynamic stability and inertness. Herein, we present a novel approach to functionalize BNQDs by hydroxyl, methyl, and amine functional groups aiming to adjust the electronic structure. The successful exfoliation is demonstrated by transmission electron microscopy, and surface functionalization is elaborated by FTIR and XPS. Modifications of the electronic and optical properties are shown by UV–Vis and PL measurements. The formation of two absorption edges in bandgaps of BNQDs due to the delocalizing of the Px and Pz orbitals as result of edge/surface passivating groups is demonstrated. Splitting of the main transition bandgap of bulk BN from 5.9 eV to two absorption edges for hydroxyl (2.3-3.6 eV), methyl (3.2-4.2 eV), and amine (3.1-4 eV) is shown. These findings offer a bandgap engineering approach for BNQDs, which can boost their applications in quantum emitters (nanophotonics) and photovoltaic devices. Graphical abstract: Image 1